2014
DOI: 10.3233/jad-131373
|View full text |Cite
|
Sign up to set email alerts
|

Aβ38 in the Brains of Patients with Sporadic and Familial Alzheimer's Disease and Transgenic Mouse Models

Abstract: The pathogenesis of Alzheimer's disease (AD) is believed to be closely dependent on deposits of neurotoxic amyloid-β peptides (Aβ), which become abundantly present throughout the central nervous system in advanced stages of the disease. The different Aβ peptides existing are generated by subsequent cleavage of the amyloid-β protein precursor (AβPP) and may vary in length and differ at their C-terminus. Despite extensive studies on the most prevalent species Aβ40 and Aβ42, Aβ peptides with other C-termini such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…In line with these data, plaque pathology-associated deposition of multiple C-terminally truncated peptides (Ab1-37, Ab1-38, Ab1-39 and Ab1-40) was previously described for familial AD (FAD) cases with the Swedish APP mutation (Reinert et al 2014;Reinert et al 2016) as well as in various transgenic mouse models carrying this mutation (Hsiao et al 1996;Kawarabayashi et al 2001;Kuo et al 2001;Reinert et al 2016).…”
Section: Discussionsupporting
confidence: 63%
“…In line with these data, plaque pathology-associated deposition of multiple C-terminally truncated peptides (Ab1-37, Ab1-38, Ab1-39 and Ab1-40) was previously described for familial AD (FAD) cases with the Swedish APP mutation (Reinert et al 2014;Reinert et al 2016) as well as in various transgenic mouse models carrying this mutation (Hsiao et al 1996;Kawarabayashi et al 2001;Kuo et al 2001;Reinert et al 2016).…”
Section: Discussionsupporting
confidence: 63%
“…Even though research has long been centered on Aβ peptides and reports on the accumulation of Aβ40 and Aβ42 are numerous, the deposition of the C-terminally truncated Aβ peptides shorter than 40 amino acids in sporadic and familial AD patients has not been thoroughly investigated in post-mortem tissue. Recent studies by Moro and colleagues [ 32 ], as well as by our group [ 44 ], reported Aβ38 to be abundantly deposited within the vasculature of SAD cases presenting severe CAA, as well as in various FAD cases with underlying APP and PSEN1 mutations. To the best of the authors’ knowledge, there are currently no studies available describing the immunohistochemical analysis of the C-terminally truncated species Aβ37 or Aβ39 in human AD cases or transgenic mouse models.…”
Section: Discussionmentioning
confidence: 88%
“…All three species have been reported to be present in cerebrospinal fluid (CSF) [ 40 , 55 ] and human plasma [ 27 ] and might be of importance to increase diagnostic accuracy when using CSF samples [ 47 ], but immunohistochemical analysis for C-terminally truncated Aβ species have so far only focused on Aβ38. For this species, Moro et al and our group recently reported abundant deposition in the vasculature in sporadic AD (SAD) cases presenting severe cerebral amyloid angiopathy (CAA), as well as within NP and vascular amyloid deposits of different FAD cases [ 32 , 44 ]. Our present study extends these findings by the analyses of the deposition of Aβ37 and Aβ39 in SAD, FAD and common animal models of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence favors the hypothesis that amyloid fibrils deposited in the vessel wall and senile plaques differ from each other, as the major species in CAA is Aβ39 or Aβ40, and in senile plaque Aβ42, although Aβ40 may also be present 23 24 . Similarly, Aβ38 seems to be predominantly located within the vasculature in postmortem brains of sporadic and familial AD patients 11 25 . Impaired vascular clearance of Aβ across the BBB and increased Aβ brain capillary deposition has been reported in transgenic mice producing low levels of the poorly cleared Dutch/Iowa mutant forms of Aβ, which are vasculotropic and rich in β-sheets 26 .…”
Section: Discussionmentioning
confidence: 97%